Child Marriage in Malaysia and the Proposed Legal Reform: Views of Muslim Stakeholders and Religious Officials - Abdol Malek, Muhammad Al-Ghazalli; Samuri, Mohd Al Adib (El-Usrah: Jurnal Hukum Keluarga, 2025)
Child marriage is widely regarded as a violation of children’s rights by the international community. The topic has generated significant public debate in Malaysia, especially following the federal government’s 2018 proposal to raise the minimum marriage age to 18 for both genders. However, this proposal faced rejection and criticism from several Muslim groups and religious authorities, who hold substantial influence over policy and law-making. This article examines the perspectives of Malaysian Muslim stakeholders on child marriage and the legal reforms aimed at ending the practice. The study involved two focus group discussions with Muslim stakeholders (n=21) and in-depth interviews with religious officials (n=22) from various Islamic authorities. The findings reveal a polarised stance on child marriage: while some stakeholders and religious officers acknowledge the practice’s harms and support legal reforms, others oppose such changes. The resistance from religious authorities and Muslim groups highlights the need for enhanced advocacy efforts on children’s rights among these influential parties to ensure successful legal reform in Malaysia.